The transformation of Traditional TV to YouTube with Social Media and its Reflections in Turkey - Kuyucu, Mihalis (Archives of Business Research, 2019)
Today, YouTube attracts more people than the mostly-watched television channels due to its audience reaching up to one billion viewers every month. YouTube is the biggest video sharing social media network of the world and has started to challenge the traditional television media with the investments it makes recently. The platform does not broadcast only the videos shared by its users but also the special programs which it produces in its production studios and took one more step further than the traditional television media with the unique contents created. This study analyses the race of YouTube platform against the traditional television media in historical processes and the youth’s habit of use of YouTube, a social media platform.